The courage of Elfina - Jacob, André (James Lorimer & Company Ltd., Publishers, 2019)
After her aunt and uncle bring her illegally from Paraguay to Canada, Elfina finds herself being treated as a slave in their home. Eventually Elfina finds the courage to talk to a priest about what is going on in her life, and he helps her find a way back home to her grandmother, father, and brother.